Vaksin Polivalen Untuk Mencegah Penyakit Flu Burung (POLIVALEN VACCINE TO PREVENT BIRD FLU DISEASES) - Suartha, I Nyoman; Wirata, I Wayan; Putra, I Gusti Ngurah Narendra; Dewi, Ni Made Ritha Krisna; Anthara, I Made Suma; Wibawan, I Wayan Teguh; Mahardika, I Gusti Ngurah Kade (Jurnal Veteriner, 2013)
This study was carried out to determine the use of bird flu polyvalent vaccines containing two or threeor more virus isolates representating of circulating viruses in the region. Three seed isolates of avianinfluenza H5N1 virus were used in this experiment. The isolates were Chicken/Denpasar/Unud-01/2004,Chicken/Klungkung/Unud-12/2006, and Chicken/Jembrana/Unud-17/2006. The seeds were inactivatedusing 0.01% formaldehide than mixed (AI3G) alumunium hidroxide adjuvant and then injectedintramuscularly to Isa Brown layer chicken at 3 weeks of age and repeated at the age of 5 weeks. The doseof each seed virus was 27 HA units. Sera were collected at one and two weeks after the second vaccination.The result showed that the arithmetic meant titer (AMT) of sera that tested with homologous isolate washigher than the test using a heterologous isolates, in the standard haemaglutination inhibition (HI) assay.The mixed AI3G vaccine produced a uniform AMT against the constituent isolates, while vaccines withindividual isolate yielded a lower and more variation in AMT. Further experiments using a commercialhomologous H5N1 and heterologous H5N2 commercial vaccines has resulted AMT that 1-4 log lower thanAI3G vaccine. It is concluded that polyvalent vaccine with field seed isolates is recommended to be appliedin the poultry farm in Indonesia.
Keywords: polivalen vaccine, bird flu, poultry